LAMDA acting anthology. Volume 4. - Karunasaagarar, Vinota; London Academy of Music and Dramatic Art. (London : London Academy of Music and Dramatic Art, 2019)
This anthology presents the set selection of solo and duologue scenes for Learners entering LAMDA Graded Examinations in Performance: Acting (from 1 August 2019), at levels 1 and 2. With a foreword by Harriet Walter, a former LAMDA graduate, the collection includes solo and duologue scenes from published plays and novels as well as scenes which have been specially written for this anthology.
Keywords: Acting -- Auditions; Monologues; Duologues